Micropore evolution in additively manufactured aluminum alloys under heat treatment and inter-layer rolling - Gu, Jianglong; Yang, Shouliang; Gao, Minjie; Bai, Jing; Zhai, Yuchun; Ding, Jialuo (Elsevier, 2019)
The application of wire + arc additively manufactured (WAAM) aluminum alloys has been restricted by the porosity defect, which is generally detrimental to the mechanical properties. Suppressing of micropores in the WAAM components has attracted considerable attention in recent years. Inter-layer rolling was introduced to eliminate micropores during the WAAM deposition of the Al–Cu6.3 and Al–Mg4.5 alloys. The distribution characteristics and individual morphology of micropores were revealed by the X-ray diffraction tomography. Key findings demonstrated that the number, volume, size, and roundness of micropores in rolled alloys decreased similarly with increasing loads, eventually achieving a density of over 99.9%. After the heat treatment, the homogeneous distribution of fine (around 5.3 μm) and spherical (0.70–0.74) micropores was realized in the 45 kN rolled alloys. All the evaluated indicators of micropores in the 45 kN rolled + heat treated alloys were superior to the post-deposition heat treated state. The evolution mechanisms include the reprecipitation of hydrogen pores, formation of vacant voids, and re-opening of unclosed pores. The hybrid technique of WAAM + rolling + heat treatment has great potential in promoting mechanical properties of WAAM alloys. The results will provide a theoretical guidance for the design of high-performance WAAM aluminum alloy components.
Keywords: Directed energy deposition; Wire + arc additive manufacture; X-ray computed tomography; Aluminum alloy; Micropores